STUDI KASUS FENOMENOLOGI ATAS OPINI AUDIT WTP DI KALANGAN PEJABAT PEMERINTAH PROVINSI JAWA TIMUR - Emy Auliyana (Universitas Negeri Malang, 2017)
This study aims to determine the meaning of unqualified opinion on the local government officials. This research is a qualitative case study approach and using the phenomenology as analysis tools to explore the meaning from the standpoint of informants. The results of this study revealed, first, unqualified opinion interpreted as a form of performance results that are technically the financial statements presented in accordance with the standards and statutory provisions. There are still the possibility of distortion, regarded as self-correction of the state apparatus for continuos improvement and not be complacent because already have unqualified opinion. Second, the study revealed that the unqualified opinion interpreted as the improvement of public welfare. Unqualified Opinion which is tried to be achieved by the East Java Provincial Government is one proof to gain the trust and recognition from society that public money is mandated been managed well.Keywords: Unqualified Opinion, Audit, Audit Opinion